Laboratory method of test for assessment of the horizontal burning characteristics of specimens no larger than 150 mm x 50 mm x 13 mm (nominal) of cellular plastics and cellular rubber materials when subjected to a small flame. (30th September 1974) - British Standards Institution,
No abstract available